Assessment of the application for renewal of authorisation of endo‐1, 4‐β‐xylanase produced by Aspergillus nigerCBS 109.713 and endo‐1, 4‐β‐glucanase produced by Aspergillus nigerDSM 18404 for poultry species, ornamental birds and weaned piglets, from BASF SE. (15th December 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Fašmon Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Natugrain ® TS/TS L is the trade name of the feed additive under assessment and contains endo‐1, 4‐β‐xylanase and endo‐1, 4‐β‐glucanase produced by genetically modified strains of Aspergillus niger . The product is currently authorised for use as a feed additive for poultry species, ornamental birds, weaned piglets and pigs for fattening. This scientific opinion concerns the renewal of the authorisation of this additive for poultry species, ornamental birds and weaned piglets. The applicant provided evidence that the additive in the market complies with the conditions of the authorisation. According to the information provided by the applicant, no new evidence has been identified that would make the FEEDAP Panel reconsider the previous conclusions regarding the safety for the target species, consumer, user and environment under the authorised conditions of use. The additive is safe for the target species for which the renewal of the authorisation is requested, the consumers and the environment. The additive is a potential skin and a respiratory sensitiser. The present application for renewal of the authorisation did not include a proposal for amending or supplementing the conditions of the original authorisation that would have an impact on the efficacy of the additive. Therefore, there was no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.